Comparative value of corn and whole and ground milo as swine-fattening feeds. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
In many parts of Kansas sorghum grains are grown extensively. In previous feeding tests with hogs at this station, some sorghum grains gave excellent results compared with corn. In 1950 Westland milo and Midland milo gave 12 percent greater daily gains than did corn. The economy in feed per 100 pounds gain was about 5 percent better from sorghum grain than from corn. Because corn has been more difficult to produce in Kansas while sorghum grains have increased in popularity it was thought advisable to get results from a 1956 experiment that compared corn with sorghum grain, with the sorghum grain prepared for feeding in different ways. Five lots of pigs were self-fed in dry lot. All lots received a mixed animal and plant protein supplement of 4 parts tankage, 4 parts soybean meal, 1 part linseed meal, and 1 part alfalfa meal. The milo was an unidentified variety, straight elevator run. Lot 1 received shelled corn; Lot 2, whole milo; Lot 3, dry rolled milo; Lot 4, wet rolled milo; and Lot 5, rolled milo with 5 percent cane molasses added.
Keywords: Swine; Corn; Milo; Gain